Perancangan Arsitektur Sistem Informasi Tugas Akhir dan Skripsi Berbasis Website di Universitas Ma’soem - Firman Hamdani (Universitas Maso'em Bandung, 2021)
One of the activities at Ma'soem University is the Registration of Final Projects for Diploma Three (D3) students and Thesis for Undergraduate students (S1). Currently, the registration process for the Final Project and Thesis is still done manually, where students must come directly to the campus to register, pay and fill out the title submission form. Meanwhile, for the preparation of seminar schedules, honoraria and final and thesis report, data processing is still using Ms. Excel. From these activities, several obstacles were found regarding information on Final Projects and Thesis, including: 1. Limited payment and registration services for Final Projects and Thesis, which can only be served on campus during working hours and days from Monday to Saturday 07.30 to 21.30 WIB. 2. Filling in the Final Project and Thesis forms manually, there is a risk of damage and loss of data. 3. Do not have a database yet, so that it is difficult to validate data on the same Final Project Title and Thesis submitted by students. 4. The process of making seminar and final project honorarium reports and thesis sessions takes a long time, and cannot be generated automatically. In this study, the system development method used is the OOAD (Object Oriented Analysis and Design) method with the RUP (Rational Unified Process) model, which consists of several stages, namely: Business Modeling, Requirments, Analysis and Design, Implementation, Test, Deployment. As for the system development tools using UML (Unified Modeling Language) which consists of: Use Case Diagrams, Activity Diagrams and Class Diagrams. With the design of the information system architecture of this Final Project and Thesis, it produces a blueprint that can: Provide payment and registration services for Final Projects and Theses that are not limited by space and time, minimize the occurrence of damage and data loss, make it easier to validate submissions for the title of Final Project the same and can facilitate the process of making seminar and final project honorarium reports and thesis reports so that they can be generated automatically.